OPTIMASI BIAYA TRANSPORTASI USAHA KELAUTAN : STUDI KASUS UDX KECAMATAN LABUHAN MARINGGAI - Alfan Andri (Fakultas Teknik Universitas Tulang Bawang Lampung, 2020)
As a maritime country, Indonesia is given an abundance of marine wealth. In an effort to distribute fish from sea products, fishermen in Labuhan Maringgai District, East Lampung Regency collect their prey to Usaha Dagang X (UDX). UDX has 3 main ordering partners for 3 categories of seafood, namely shrimp, fish and crab. Transportation problems at UDX cause distribution costs to increase in delivery of goods to the customer. This study provides an alternative minimum cost solution that can be issued by UDX in distributing goods that are available using existing limitations. The results showed that the minimum shipping cost was IDR 5281200 where the 3 proposed methods showed the same results but had different alternative options.